Evolution of the COPD Assessment Test Score during Chronic Obstructive Pulmonary Disease Exacerbations: Determinants and Prognostic Value. Issue 5 (2013) - Feliz-Rodriguez, Darwin; Zudaire, Santiago; Carpio, Carlos; Martínez, Elizabet; Gómez-Mendieta, Antonia; Santiago, Ana; Alvarez-Sala, Rodolfo; García-Río, Francisco
Abstract : BACKGROUND: An adequate evaluation of exacerbations is a primary objective in managing patients with chronic obstructive pulmonary disease (COPD). OBJECTIVES: To define the profile of health status recovery during severe exacerbations of COPD using the COPD Assessment Test (CAT) questionnaire and to evaluate its prognostic value. METHODS: Forty-five patients with previous COPD diagnoses who were hospitalized due to severe exacerbation(s) were included in the study. These patients were treated by their respective physicians following current recommendations; health status was assessed daily using the CAT questionnaire. The CAT score, spirometry and recurrent hospitalizations were recorded one and three months after hospital discharge. RESULTS: Global initiative for chronic Obstructive Lung Disease (GOLD) stage was an independent determinant for increased CAT score during the first days of exacerbation with respect to postexacerbation values. From hospitalization day 5, the CAT score was similar to that obtained in the stable phase. Body mass index, GOLD stage and education level were related to health status recovery pattern. CAT score increase and the area under the curve of CAT recovery were inversely related to the forced expiratory volume in 1 s achieved three months after discharge (r= −0.606; P<0.001 and r= −0.532; P<0.001, respectively). Patients with recurrent hospitalizations showed higher CAT score increases and slower recovery. CONCLUSIONS: The CAT detects early health status improvement during severe COPD exacerbations. Its initial worsening and recovery pattern are related to lung function and recurrent hospitalizations.